DFT INVESTIGATION OF CO2 REDUCTION TO CO AND HCOOH ON TRANSITION METAL DOPED NICKEL PHOSPHATE SURFACE - Ilhami, Hardika
To reduce CO2 levels in the atmosphere, one possible approach is CO2 utilization. CO2RR is a concept that can be applied within it. In this process, an electrocatalytic system requires a catalyst with good selectivity and low overpotential. Nickel (II) Phosphate, has shown great potential in other reactions due to its reliable track record. However, its effectiveness as a catalyst specifically for CO2 reduction has not yet been explored, leaving its catalytic potential in this context yet to be determined. We investigated the activity and selectivity of carbon dioxide reduction reaction (CO2RR) on the active sites of Nickel (II) Phosphate facet 100 or NiPO (100) in its pure form, as well as NiPO (100) doped with transition metals through substitutional defect methods, using a combination of DFT calculations. The calculations were performed in two modes: CO formation and HCOOH formation. The limiting potentials of these two formation reactions are explained in terms of the adsorption energies of COOH, CO, and their combinations for CO formation, as well as the adsorption energies of HCOO, OH, and their combinations for HCOOH formation. The success rate of CO2RR depends on the catalyst's ability to suppress the parasitic HER reaction. We found that the addition of transition metal doping can enhance the catalytic activity of CO2RR. Furthermore, several configurations of active sites show good potential in CO2RR due to their low HER limiting potentials. Keywords: CO2RR, Active NiPO Site (100), Subtitution Defects, Transition Metal Doping, DFT